2017
DOI: 10.1016/j.dhjo.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Aging, mobility impairments and subjective wellbeing

Abstract: Background Wellbeing is often described as U-shaped over the life course, suggesting an apparent paradox that wellbeing remains high at older ages despite increases in impairments. Objective/Hypotheses We explore associations among age, lower body impairments—one of the most common late-life impairments—and three measures of wellbeing: life satisfaction, emotional wellbeing and somatic wellbeing. We hypothesize that age effects are positive, become stronger once lower body impairments are controlled, and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…Older adults with impairments that are not accommodated may struggle to carry out daily activities, maintain social relationships, and live independently. They also may quit work or abandon leisure activities that were once a source of pleasure and may feel their independence and autonomy are undermined (Freedman et al, ). Consequently, impairment is associated with heightened depressive symptoms and compromised daily mood, life satisfaction, and self‐esteem (Freedman et al, ; Mancini & Bonanno, ), with prospective studies documenting that effects operate from disability to distress rather than vice‐versa (Gayman, Turner, & Cui, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults with impairments that are not accommodated may struggle to carry out daily activities, maintain social relationships, and live independently. They also may quit work or abandon leisure activities that were once a source of pleasure and may feel their independence and autonomy are undermined (Freedman et al, ). Consequently, impairment is associated with heightened depressive symptoms and compromised daily mood, life satisfaction, and self‐esteem (Freedman et al, ; Mancini & Bonanno, ), with prospective studies documenting that effects operate from disability to distress rather than vice‐versa (Gayman, Turner, & Cui, ).…”
Section: Introductionmentioning
confidence: 99%
“…Impairment also compromises older adults' emotional well‐being and is linked with heightened depressive symptoms, sadness, and frustration, and reduced happiness (Bierman, ; Freedman, Carr, Cornman, & Lucas, ). However, the strength of these associations is diminished for those who are married (Bierman, ) and whose marriages are supportive rather than strained (Bookwala, ; Carr, Cornman, & Freedman, ).…”
mentioning
confidence: 99%
“…But this pattern is not universal. A study challenges the notion that wellbeing is U-shaped throughout the life course and underscores the critical role of mobility across wellbeing domains in later life [62]. The above shows that there is a significant correlation between happiness and life expectancy.…”
Section: Moderating Hypothesismentioning
confidence: 89%
“…The evidence from recent studies has identified the elderly's interest in different type of physical activity that are simple, easy and help them in developing well-being and internal satisfaction than focused on fitness and appearances [13][14][15][16][17]. Well-being, which is consisted of physical, psychological and social components [18], and high well-being are associated with low prevalence of non communicable diseases, healthy aging and longevity [19,20].…”
Section: Introductionmentioning
confidence: 99%